2020
DOI: 10.1088/1361-6528/ab8cf3
|View full text |Cite
|
Sign up to set email alerts
|

Spiky-shaped niobium pentoxide nano-architecture: highly stable and recoverable Lewis acid catalyst

Abstract: Niobium pentoxide particles with a complex three-dimensional (3D) nanostructure consisting of a spiky structure have been developed as recyclable and recoverable Lewis acid catalysts. The morphology of the niobium pentoxide was successfully controlled from 1D to 3D via a bridging-ligand-assisted hydrothermal treatment, without changing the crystal structure. Compared with dispersed one-dimensional (1D) niobium pentoxide nanorods with a major-axis length and minor-axis length of 20 nm and 5–8 nm, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…Increasing the temperature to 190 °C, the approximate major axis length increased to 30 nm, and the nanorods were separated from each other (Figure 1j–l and S4, Supporting Information). There was no change in morphology between 190 and 200 °C samples, and as in previous reports, [ 14,17,18 ] the spiky Nb 2 O 5 nanoparticles composed of a spherical core and numerous nanorods were obtained (Figure 1m–o and S5, Supporting Information). These results suggested that the nanorods grew by migration not only from a spherical core but also among primal particles, rectangular‐shaped nanoarchitectures, and nanorods.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Increasing the temperature to 190 °C, the approximate major axis length increased to 30 nm, and the nanorods were separated from each other (Figure 1j–l and S4, Supporting Information). There was no change in morphology between 190 and 200 °C samples, and as in previous reports, [ 14,17,18 ] the spiky Nb 2 O 5 nanoparticles composed of a spherical core and numerous nanorods were obtained (Figure 1m–o and S5, Supporting Information). These results suggested that the nanorods grew by migration not only from a spherical core but also among primal particles, rectangular‐shaped nanoarchitectures, and nanorods.…”
Section: Resultssupporting
confidence: 88%
“…In our previous studies, hydrothermal treatment of the ammonium niobate ( V ) oxalate solution without the acetates produced shorter Nb 2 O 5 nanorods (20 nm in major axes length) than the nanorods synthesized with acetates. [ 14 ] Furthermore, secondary particle growth was not suppressed on the shorter Nb 2 O 5 nanorods, resulting in nanorods aggregation. Thus, the acetate ions must adsorb onto the surface of Nb 2 O 5 particles and function as protecting agents to suppress the particle growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have fabricated spiky-shaped Nb 2 O 5 nanoparticles composed of numerous nanorods on a sub-micro sized spherical core by hydrothermal treatment of Nb oxalate solution. [9][10][11] The 3D nanostructure has higher stability compared to dispersed nanorods. However, high catalytic activity was not observed in the spiky-shaped Nb 2 O 5 nanoparticles, even though they have a single nanoscale structure and large surface area.…”
Section: Introductionmentioning
confidence: 99%